Efektivitas Penerapan Model Pembelajaran Teams Game Tournament (Tgt) Dan Talking Stik (Ts) Dalam Meningkatkan Motivasi Belajar Peserta Didik Pada Mata Pelajaran Ski Di Kelas X IPA 2 MAN 2 Karawang - Lestari, Riska Puji; Sitika, Achmad Junaedi; Nurhasan, Nurhasan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The problem in this study is the lack of student learning motivation which is illustrated by the condition of students who are less active and less responsive when SKI learning takes place. The purpose of this study was to describe the application of the Teams Game Tournament (TGT) and Talking Stik (TS) cooperative learning models in SKI subjects in class X IPA 2 MAN 2 Karawang and to describe the effectiveness of implementing the Teams Game Tournament (TGT) and Talking cooperative learning models. Stick (TS) on SKI subjects in class X IPA 2 MAN 2 Karawang. This study uses experimental research with a mix method approach. The data collection techniques used were observation, interviews and tests while the data analysis techniques for observations and interviews used interactive analysis according to Miles and Huberman, for tests using the N-gain test with the help of the SPSS 18 application program. The results of this study indicate that the application of the Teams learning model Game Tournament (TGT) and Talking Stick (TS) in SKI subjects in class X IPA 2 are carried out with the following steps, first the teacher first conveys a learning material about Caliph Usman bin Affan and Caliph Ali bin Abi Thalib, then after the material is delivered the students are divided into several groups, the teacher has provided several questions (quizzes) and sticks for each group, then the sticks are played in each group while singing the song that has been agreed with the teacher, then the teacher dismisses the song and the student who last held the stick when stopped by the teacher is the one who has the right to answer the questions (quizzes) that have been provided and the use of the Teams Games Tournament (TGT) and Talking Stick (TS) methods is quite effective in increasing the learning motivation of class X students IPA 2 MAN 2 Karawang in SKI subjects, while the use of lecture and question and answer methods is not effective for increasing the learning motivation of class X IPA 1 MAN 2 Karawang students in SKI subjects